PENGEMBANGAN BUDIDAYA JAMUR TIRAM PUTIH SEBAGAI AGRIBISNIS PROSPEKTIF BAGI GAPOKTAN SEROJA I KANDANG LIMUN BENGKULU - Sariasih, Yenny (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
This activity aims to foster the farmers who are members of Gapoktan Seroja I Kandang Limun, Bengkulu to initiate oyster mushroom cultivationas one of the prospective agribusinesses in Bengkulu. This business was chosen due to the fungus growing medium are available in huge quantities and being waste around Kandang Limun. Further, Oyster mushroom demand and price are high. This event is a program of Ipteks bagi Masyarakat (IBM) in collaboration with the Lembaga Pengabdian Masyarakat (LPM). Training activities include the cultivation, manufacture kumbung measuring 3x4m which capacity of 2000 baglogs, baglog manufacture, sterilization baglog, inoculation, incubation for 3-6 weeks until the harvesting and marketing. Gapoktan Seroja I have been able to make ± 1500 baglog and have been able to produce white oyster mushroom ± 5 to10 kg per day. Fresh mushrooms sold at Rp. 20,000- 24.000/kg. With good management and sustainable production, the oyster mushroom cultivation can be one of the prospective agribusiness for Gapoktan Seroja I Kandang Limun, Bengkulu.